Dakwah Kultural di Bumi Melayu: Modal Sosial Gerakan Pemuda Ansor Riau dalam Melestarikan Tradisi Shalawatan: Cultural Da’wah in Malay Land: Social Capital of the Gerakan Pemuda Ansor Riau in Preserving the Shalawatan Tradition - Adrian Firman Rokandi; Yusmar Yusuf; Tengku Romi Marnelly (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The shalawatan tradition represents a vital form of religious expression and cultural identity within Nahdlatul Ulama that continues to thrive amid modern social change. This study explores how social capital sustains the shalawatan tradition organized by the Gerakan Pemuda Ansor (Ansor Youth Movement) in Riau Province. It focuses on three main dimensions of social capital. Trust, social networks, and social norms. Along with strategies to strengthen them. Using a qualitative approach, data were collected through observation, in-depth interviews, and documentation from 20 informants: the regional GP Ansor leader, kyai figures, pesantren networks, regular congregants, and local branch heads in Siak and Pelalawan. The analysis employed the social capital frameworks of Putnam, Coleman, and Fukuyama. The findings show that trust is the most dominant form of social capital, reflected in the integrity of leaders, financial transparency, and consistent spiritual service free of political interests. Strengthening social capital is achieved through maintaining trustworthy leadership, expanding inclusive networks, integrating Islamic education into activities, and promoting collective participation through mutual assistance. The continuity of shalawatan is also supported by charismatic kyais and institutional backing from Nahdlatul Ulama, though challenges persist in community resistance and limited managerial capacity. This study highlights that the interplay among trust, networks, and norms generates effective collective action, ensuring the resilience of religious traditions amid modernization.